Putting Leininger's nursing theory 'culture care diversity and universality' into operation in the curriculum - Part 1 - L. de Villiers; D. van der Wal (AOSIS, 1995)
The culturally diverse South African society necessitates inclusion of transcultural nursing in the curriculum. This article focuses on research regarding the putting of Leininger's nursing theory into operation in the curriculum to provide a scientific base for the inclusion of such nursing. The research process and results are discussed.